High-resolution photoreceptor imaging analysis of patients with autosomal dominant retinitis pigmentosa (adRP) caused by HK1 mutation. (1st November 2020) - Kubota, Daiki; Matsumoto, Kaori; Hayashi, Mika; Oishi, Noriko; Gocho, Kiyoko; Yamaki, Kunihiko; Kobayakawa, Shinichiro; Igarashi, Tsutomu; Takahashi, Hiroshi; Kameya, Shuhei
ABSTRACT: Purpose: The hexokinase 1 ( HK1 ) gene encodes one of the four human hexokinases that play essential roles in glucose metabolism. Recently, several cases of E847K mutation in the HK1 gene were reported to cause inherited retinal dystrophy. The purpose of this study was to identify the phenotypical characteristics of patients with a recurrent E847K mutation in the HK1 gene. Methods: Three generations of one family with autosomal dominant retinitis pigmentosa were examined. Whole exome sequencing was performed on the DNA. Fundus imaging by an adaptive optics fundus camera was used to obtain high-resolution photoreceptor images. Results: Fundus examination of the proband showed degeneration of the mid-peripheral retina, and SD-OCT images showed an absence of the ellipsoid zone (EZ) and interdigitation zone (IZ) in the parafovea and more peripherally. SD-OCT images of the mother of the proband showed an absence of the EZ and IZ, and fundus autofluorescence images showed hypo-autofluorescence surrounding the macular region. One daughter of the proband had only mild night blindness, however, the density of the cone photoreceptors was reduced in the parafoveal region. Whole exome sequencing identified a heterozygous variant, E847K, in the HK1 gene. This variant was found to co-segregate with the disease in three family members. Conclusions: Although the systemic phenotypes were found to be associated with the HK1 mutations, only the E847K mutation can cause a non-syndromic photoreceptor degeneration. Our study strengthened the hypothesis that the amino acid E847 might play a critical role in the maintenance of the morphology and function of the photoreceptors.